2014
DOI: 10.3171/2014.3.jns131289
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of incidental colloid cysts

Abstract: Object Incidental colloid cysts are frequently managed with surveillance imaging rather than surgical excision. This approach is born out of their purported indolent growth pattern and the surgical morbidity associated with microsurgical removal. The advent of endoscopic colloid cyst removal may offer renewed assessment of these patients who carry a risk of acute neurological deterioration. An evidence-based recommendation should weigh the risks of operative treatment. Thus far, there has been no concentrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
(33 reference statements)
0
22
3
Order By: Relevance
“…11 On the other hand, our data are in direct contrast to the recent study by Margetis et al that reported neither patient age nor cyst diameter was correlated with the absence or presence of symptoms in patients with colloid cysts. 12 Although the ages of our symptomatic cohorts were similar (37.9 ± 15.5 vs 43.3 ± 15.7 years), the incidental cohort was significantly older in the present study (54.2 ± 19.8 vs 39.7 ± 14.5 years), which may account for the significant difference in age that we observed. This discrepancy could be explained by differences in the demographics of the respective regions (St. Louis, Missouri vs New York City), differences in referral patterns, and the fact that our institution is a regional trauma center that serves both an urban and rural catchment area.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…11 On the other hand, our data are in direct contrast to the recent study by Margetis et al that reported neither patient age nor cyst diameter was correlated with the absence or presence of symptoms in patients with colloid cysts. 12 Although the ages of our symptomatic cohorts were similar (37.9 ± 15.5 vs 43.3 ± 15.7 years), the incidental cohort was significantly older in the present study (54.2 ± 19.8 vs 39.7 ± 14.5 years), which may account for the significant difference in age that we observed. This discrepancy could be explained by differences in the demographics of the respective regions (St. Louis, Missouri vs New York City), differences in referral patterns, and the fact that our institution is a regional trauma center that serves both an urban and rural catchment area.…”
Section: Discussioncontrasting
confidence: 54%
“…Estimates of the risk of rapid clinical deterioration due to acute hydrocephalus in patients with colloid cysts vary widely, from 3% to 35%, with an associated 5%-38% risk of death. 2,4,12,13,17 Historically, these patients were often described as having experienced "sudden deterioration and death," but several more recent studies using modern neuroimaging techniques have demonstrated that nearly all patients with acute obstructive hydrocephalus have progressive symptoms preceding precipitous clinical deterioration. Potential exceptions are the rare instances of acute intralesional hemorrhage or "cyst apoplexy."…”
mentioning
confidence: 99%
“…Some studies have suggested that an incidental finding of colloid cyst should not result in a resection but rather in observation with serial imaging (8,27) while others have been more in favor of a surgical approach (28,29). Margetis et al compared surgical outcomes in 20 patients with incidental colloid cysts to 57 symptomatic patients with colloid cysts.…”
Section: Incidental Diagnosismentioning
confidence: 99%
“…Margetis et al compared surgical outcomes in 20 patients with incidental colloid cysts to 57 symptomatic patients with colloid cysts. They found that there were no significant differences in postoperative morbidity and mortality (28). However, a major question that remains unanswered is whether there are any significant differences in benefits from such a procedure for patients with an incidental diagnosis.…”
Section: Incidental Diagnosismentioning
confidence: 99%
“…Colloid cysts have traditionally been operated through open microsurgery (OS), but advances with the endoscopic equipment and introduction of technical nuances to the endoscopic approach have made this approach the first-hand choice in several neurosurgical centers [8][9][10][11] . There is currently no consensus on the approach of choice that yields the most favourable results, in the treatment of patients with colloid cysts.…”
Section: Introductionmentioning
confidence: 99%